Digital Reflections: Role of Social Media in Shaping Women's Self-Image and Mental Health - Nadaf, Zaffar Ahmad; Nazir, Usma; Behera, Santosh Kumar (PT. Riset Press International, 2025)
This study aims to explore the impact of social media on women's self-image and mental health, examining how different social media platforms influence perceptions of body image, self-esteem, and psychological well-being. The PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) methodology was used to conduct and report systematic reviews. A comprehensive search was conducted across multiple electronic databases, including PubMed, PsycINFO, Web of Science, and Google Scholar. The search strategy involved using specific keywords such as